KONSEP PENDIDIKAN ISLAM BAGI REMAJA PERSPEKTIF QUR’AN SURAT YUSUF AYAT 23-29 (KAJIAN TAFSIR AL AZHAR) - Siti Lailiyah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2018)
This study intends to examine verse verses that tell of the Prophet Joseph who is able to resist the temptation of women who disturb him and able to restrain lust. This is so that it can be applied in adolescent education to instill religious, ethical or moral values in their souls so that the goal of Islamic education to form young people into human beings can be realized, and they are not easily seduced by lust. In this study the authors chose Tafsir Buya Hamka to be the main literature. The results of this study can be put forward as follows: (1) In writing the Tafsir of Joseph, especially verses 23-29, Buya Hamka advised his children, grandchildren and students about the importance of father education for children when children are young. This is based on Buya Hamka's own experience when he was 10 years old, he witnessed his father's piety and violence in educating his children. His father's former training was still felt until he was 65 years old. (2) The educational values contained in the Qur'an Letter Yusuf verses 23-29 are: the importance of politeness, tawadlu '(humble), not arrogant, faith in Allah SWT, patient, discipline, trustworthy, honest, self-preserving accompanied by strong faith, self-defense, endeavor accompanied by courage in upholding the truth, gratitude, the need for a neutral attitude in decision making, tasamuh nature, the importance we instill awareness, repentance and the need to uphold justice.